(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study investigates the impact of the Kolawole Problem Solving (KPS) method on students’ attitudes towards Biology in secondary schools in Ondo State, Nigeria. The study addresses three specific objectives: (i) examining the difference in attitudinal mean scores between students exposed to KPS and those using conventional methods in Biology, (ii) analyzing gender-based variations among students using the KPS method, and (iii) evaluating differences in attitudinal mean scores between students in rural and urban schools using the KPS strategy. A quasi-experimental design with a pre-test, post-test, control group structure was employed, involving an experimental group using the KPS technique and a control group using traditional methods. The study’s population comprised Senior Secondary School Two (SSS II) students enrolled in Biology courses at public secondary schools in Ondo State. The sample included 139 SSS II students from six public schools, selected through a multistage sampling procedure. Data were collected using the Students’ Attitude Towards Biology Scale (SATBS). The results revealed a significant difference in attitudinal mean scores between students exposed to KPS and those using conventional methods, with the KPS group exhibiting a more positive attitude toward Biology. However, no significant gender-based differences were observed among students using the KPS method, and there were no significant variations in attitudinal mean scores based on geographical location. In conclusion, the implementation of the Kolawole Problem Solving approach positively influenced students’ attitudes toward Biology, without gender bias and regardless of location. This suggests the potential benefits of incorporating the KPS method into Biology curricula and providing comprehensive teacher training to effectively utilize this approach.